The power of combined molecular and morphological analyses for the genus Botrylloides: identification of a potentially global invasive ascidian and description of a new species. Issue 5 (4th July 2019) - Rocha, Rosana M.; Salonna, Marika; Griggio, Francesca; Ekins, Merrick; Lambert, Gretchen; Mastrototaro, Francesco; Fidler, Andrew; Gissi, Carmela
Abstract : Botryllids are colonial styelid ascidians for which morphological characters distinguishing genera and species are often difficult to identify and frequently ambiguous. Botrylloides perspicuus, Botrylloides giganteus, and Botrylloides pizoni have similar colony and zooid appearances and over recent years have been found in dispersed localities around the world. In order to determine how many valid Botrylloides species there are, and how they are geographically distributed, we performed both molecular and morphological analyses on fresh and archival museum specimens of these Botrylloides coming from six distant localities: southern Italy, southern California, Brazil, Galapagos Islands, New Zealand, and Australia. Moreover, we re-analysed the morphology of a number of formalin-preserved museum specimens. We concluded that both B. perspicuus and B. giganteus are indeed valid species and report morphological and molecular characters that distinguish these species; B. pizoni is concluded to be a junior synonym of B. giganteus . The geographic distribution, collection dates, and growth substrates of B. giganteus indicate that this species is rapidly spreading worldwide and has traits that may enhance invasiveness (i.e., presence in intertidal regions; high tolerance to air exposure, temperature and salinity variation). Therefore, B. giganteus should be a focus of both researchers and managers concerned with marine biosecurity. Interestingly, the morphological re-analyses of archival museum samples guided by molecular results, led to the taxonomic reassignment of several botryllid specimens as well as to the identification of a new species, Botrylloides conchyliatus sp. nov., which is here described. http://www.zoobank.org/urn:lsid:zoobank.org:pub:0D896E42-F460-45E2-B74C-576A011D9214